Reduced complexity APP for turbo equalization - Raphaeli, D.; Saguy, A. (2002 IEEE International Conference on Communications, 2002)
This paper investigates the subject of reducing the complexity of turbo equalization in which a receiver combines the equalization and decoding process in an iterative fashion. We show that it is possible to approximate the a posteriori probability (APP) module by two time varying linear transversal filters and a simple nonlinear memoryless processor, and thus replace the exponential complexity of the APP module with quadratic complexity in the filter length. Further complexity reduction leads to linear complexity, for which the transversal filters are constant during the block. For this structure, which is similar to a previously suggested scheme, we calculate the optimized parameters and increase performance. The derivations cover the cases of BPSK and QAM modulations. Simulation results are presented for parallel-concatenated turbo code with BPSK and QAM modulation over channels that introduce severe amplitude distortion.